CORRELATIONS OF SOCIO-ENVIRONMENTAL IMPACTS AND MINING ACTIVITIES (Interdisciplinary Studies Journal, 2024)
In this work, we correlated some socio-environmental impacts, indicated by some studies referring to the exploitation of mineral resources.The methodology used is critical and literary review, with analytical processes of a qualitative nature. We observe that mining activities have increased, ensured and “legitimized” by legal guidelines. Complex circumstances and mining contexts, as well as legal principles and guidelines, demand rigorous historical and critical investigations. We noticed that categories of Laws and legal norms, from statist Law, which are extremely harmful, are permeated with imperative abstractions and primacy, in the form of “acquired rights” and “legalities”, ensuring large-scale exploitation of natural resources and a imposition of a highly contested legal “legitimacy”.
Keywords: Mining; Exploration; Laws; Environment